Questionnaire for evaluation of musculoskeletal pain in exercise practitioners (Q-ADOM) Questionário para avaliação da dor musculoesquelética em praticantes de exercício (Q-ADOM) Cuestionario para la evaluación del dolor musculoesquelético en practicantes de ejercicio (Q-ADOM) - Lima D.P.* (2016)
© 2016, Redprint Editora Ltda. All rights reserved.Introduction: Cardiovascular diseases have been associated with the presence of musculoskeletal disorders. The presence of pain in these comorbidities may be a limiting factor for exercise practice. However, no instruments were found that provide more thorough measurement and accurate information that can be easily used in clinical practice. In this sense, the construction and validation of a more specific instrument becomes relevant to obtain detailed information on the presence and severity of these symptoms and its interference in the functional aspects, costs, and psychosocial factors at different times that result in a more precise evaluation. Thus, professionals of the multidisciplinary team involved in cardiopulmonary and metabolic rehabilitation (CPMR) programs can use it in clinical practice and put aside the strategies specifically directed to these conditions. Objectives: To construct and validate an instrument to assess musculoskeletal pain at rest and during exercise in participants of CPMR. Methods: Theoretical, empirical, and analytical procedures were performed. The concordance analysis among evaluators (judges) was verified by Kendall’s W test, the internal consistency of the items through Cronbach’s alpha, and reproducibility and stability measures through the test and retest (intraclass correlation coefficient-ICC and Kappa coefficient). Results: The concordance among evaluators was significant (p=0.001) and showed satisfactory internal consistency values (Cronbach’s alpha > 0.82). The test-retest indicated good reproducibility and stability measures (ICC<0.40 and Kappa<0.60). Conclusion: The questionnaire for the evaluation of musculoskeletal pain in exercise practitioners (Q-ADOM) proved to be valid, reproducible, and reliable to be used in the evaluation of musculoskeletal pain in CPMR participants.